The Digital Divide: AI Risk Stratification vs. Traditional Clinical Scoring - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Digital Divide: AI Risk Stratification vs. Traditional Clinical Scoring Introduction: The Evolution of Risk Assessment in Digital Health The landsca...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics